Changes in brain activation in breast cancer patients depend on cognitive domain and treatment type - Menning, Sanne (PLoS One, 2017)
BACKGROUND: Cognitive problems in breast cancer patients are common after systemic treatment, particularly chemotherapy. An increasing number of fMRI studies show altered brain activation in breast cancer patients after treatment, suggestive of neurotoxicity. Previous prospective fMRI studies administered a single cognitive task. The current study employed two task paradigms to evaluate whether treatment-induced changes depend on the probed cognitive domain. METHODS: Participants were breast cancer patients scheduled to receive systemic treatment (anthracycline-based chemotherapy +/- endocrine treatment, n = 28), or no systemic treatment (n = 24) and no-cancer controls (n = 31). Assessment took place before adjuvant treatment and six months after chemotherapy, or at similar intervals. Blood oxygen level dependent (BOLD) activation and performance were measured during an executive functioning task and an episodic memory task. Group-by-time interactions were analyzed using a flexible factorial design. RESULTS: Task performance did not differ between patient groups and did not change over time. Breast cancer patients who received systemic treatment, however, showed increased parietal activation compared to baseline with increasing executive functioning task load compared to breast cancer patients who did not receive systemic treatment. This hyperactivation was accompanied by worse physical functioning, higher levels of fatigue and more cognitive complaints. In contrast, in breast cancer patients who did not receive systemic treatment, parietal activation normalized over time compared to the other two groups. CONCLUSIONS: Parietal hyperactivation after systemic treatment in the context of stable levels of executive task performance is compatible with a compensatory processing account of hyperactivation or maintain adequate performance levels. This over-recruitment of brain regions depends on the probed cognitive domain and may represent a response to decreased neural integrity after systemic treatment. Overall these results suggest different neurobehavioral trajectories in breast cancer patients depending on treatment type.